The effect of JGP slab on the stability of deep excavation - Lim, Samuel Bi Yao (2015)
This report presents the results of a preliminary analysis of the effects of varying Jet Grouted Piles (JGP) on the stability of braced excavation using finite element method. The use of PLAXIS 2D to simulate and idealise the soil profile and the parameters gives the user a better estimate of the actual performance of any excavation. Two idealised soil profiles were used: a uniform soil system and a two-layer soil system. For the excavation done in the uniform soil system, the JGP properties are varied and compared. For the two-layer soil system, the struts were installed with prestress and then the thickness of the JGP is reduced in another case. The wall depth was also shortened to explore the variation and the results were compared. The extraction of key parameters data gives the user a gauge of the performance of the excavation at various stage of the excavation. Sacrificial JGP is also explored to understand how removal of JGP affects the stability of the excavation and the soil around the excavation. The results reflected in the finite element software tells of the varying changes to the stability of the excavation with changes in properties. A general use of JGP improves the excavation stability tremendously. An increase in thickness and shear strength parameter of the JGP will yield a more stable excavation, but at the expense of more internal forces in the wall. Prestressed struts and reduction in wall depth causes minor changes to the results. But a generally increase or improvement in materials or properties will yield an increase in the stability. The converse is also true. Sacrificial JGP removal is show to have adverse effects on the stability of the excavation if not accounted for properly. Further analysis of more excavation profile under different soil conditions need to be carried out to confirm these findings.